Analytic methods for the Percus-Yevick hard sphere correlation functions - Henderson, D. (Condensed Matter Physics, 2009)
The Percus-Yevick theory for hard spheres provides simple accurate expressions for the correlation functions
that have proven exceptionally useful. A summary of the author's lecture notes concerning three methods of
obtaining these functions are presented. These notes are original only in part. However, they contain some
helpful steps and simplifications. The purpose of this paper is to make these notes more widely available. Теорiя Перкуса-Євiка для твердих сфер дає можливiсть отримати дуже кориснi простi точнi вирази для кореляцiйних функцiй. Тут представлено пiдсумковi нотатки лекцiй, що стосуються трьох методiв отримання цих функцiй. Представленi нотатки є тiльки частково оригiнальними. Проте, вони мiстять кориснi кроки i спрощення. Метою цiєї статтi є зробити цi нотатки бiльш доступними широкому загалу.